UV-VIS spectroscopic studies of diamide ligands as potential tools for anion sensor - Abdul Kadir Maisara, Mohd Salleh Mohamad Nur Azshary, Kassim Nur Syazwani, (Universiti Pendidikan Sultan Idris, 2016)
UV-VIS spectroscopic studies of diamide ligands as potential tools for anion sensor by Abdul Kadir Maisara, Mohd Salleh Mohamad Nur Azshary, Kassim Nur Syazwani,